How Efficient is the East German Economy? An Exploration With Micro Data - Michael Funke; Jörg Rahn (Center for Economic Studies and ifo Institute (CESifo), 2000)
The purpose of this paper is to evaluate the efficiency of the East German economy at the firm level using an unbalanced panel over the transition period 1994 to 1998. We adopt a translog stochastic frontier model to estimate technical efficiency in eastern and western Germany. The results indicate that firms in eastern Germany are significantly less efficient than firms in western Germany. The paper also examines some of the possible correlates of regional variations in firm-level efficiency.
Keywords: 330; East Germany; technical efficiency; panel data; convergence; wages